SUBSIDIZING ALTRUISM IN LIVING ORGAN DONATION. (30th August 2017) - Schnier, Kurt E.; Merion, Robert M.; Turgeon, Nicole; Howard, David
Abstract : The current supply of deceased donor organs is insufficient to meet the growing demand for transplantable organs. Consequently, candidates for kidney transplantation are encouraged to find a living donor. In 2008, the Department of Health and Human Services began to reimburse donors' travel‐related expenses via the National Living Donor Assistance Center (NLDAC). Using variation in transplant centers' applications for donor assistance, we use a difference‐in‐difference model to estimate the relationship between the NLDAC and living donor kidney transplants. We find that among participating transplant centers, the program increased the number of living donor kidney transplants by approximately 14%. ( JEL I12, I18, D64)